Analysis of the Effect of Internet Social Networks on Societal Development - Ikenna, Oluigbo; Chinyere, Okpara; Ikenna, Ajere (IJRDO - Journal of Applied Management Science, 2015)
Social Network is an Internet application in the field of Information Technology to study andassess relationships between individuals, groups, organizations, or even entire societies.Social media offers a range of new possibilities for individuals and organisations working forsocial good. The aim of this research is to identify a number of social networks in existence,and evaluate the individual and collective effects (both positive and negative effects) thesesocial networks have on societal growth and development. Five social networks wereidentified; Facebook, Twitter, Bebo, Hi5 and MySpace, which forms the independentvariables. The study used a population size of 100 respondents, with a sample size of 80respondents. Data were collected and analyzed through quantitative and qualitative methodsand the use of regression analysis was used in testing of the hypothesis at a 0.05 significantlevel. From the researchers’ findings, the respondents agreed that there is a significant effectof individual social network and the collective social networks on societal development.Therefore, social networks can be an effective tool for individual and organisation’s growth,as well as having a sizeable impact on the development of a society.